2017
DOI: 10.1016/j.carbpol.2016.09.067
|View full text |Cite
|
Sign up to set email alerts
|

Novel cellulose-based amorphous solid dispersions enhance quercetin solution concentrations in vitro

Abstract: Quercetin (Q) is a bioactive flavonol with potential to benefit human health. However, Q bioavailability is relatively low, due to its poor aqueous solubility and extensive phase-II metabolism. Strategies to increase solution concentrations in the small intestinal lumen have the potential to substantially increase Q bioavailability, and by extension, efficacy. We aimed to achieve this by incorporating Q into amorphous solid dispersions (ASDs) with cellulose derivatives. Q was dispersed in matrices of cellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…One of the most important characters of CAP is that it can function as an enteric coating because of the presence of ionizable phthalate groups. Its solubility depends on the pH of the media, which is insoluble in acid media (pH ≤ 5) but is soluble when the pH is ≥6 (Gilley et al., 2017). In this sense, CAP is able to protect encapsulated core material against the gastric acid in stomach and gradually release the core material in the slightly neutral to alkaline conditions in the intestines.…”
Section: Characteristic Properties and Species Of Polysaccharides Formentioning
confidence: 99%
“…One of the most important characters of CAP is that it can function as an enteric coating because of the presence of ionizable phthalate groups. Its solubility depends on the pH of the media, which is insoluble in acid media (pH ≤ 5) but is soluble when the pH is ≥6 (Gilley et al., 2017). In this sense, CAP is able to protect encapsulated core material against the gastric acid in stomach and gradually release the core material in the slightly neutral to alkaline conditions in the intestines.…”
Section: Characteristic Properties and Species Of Polysaccharides Formentioning
confidence: 99%
“…Conventional HPβCD significantly enhanced solubilization efficiency as compared to pure dexibuprofen in all solutions. [32][33][34] Formerly, significantly improved solubilization efficiency of paclitaxel was demonstrated by nanoparticles of star polymer of βCD-poly(N-isopropylacrylamide) by forming supramolecular inclusion complexes. It was suggested that hybrid nanogels facilitated inclusion ability of HPβCD.…”
Section: Solubilization Enhancementmentioning
confidence: 99%
“…However, this small group of polymers is not sufficiently structurally diverse to enable systematic study of structure activity relationships, and these polymers were not specifically designed for ASD formulation, but rather were repurposed from other pharmaceutical applications. In recent years, synthesis of novel polymers specifically designed for use in ASDs, as well as to facilitate mechanistic understanding of key polymer functionality, has led to an increase in polymer diversity 11 , 15 . Ultimately, if polymers with enhanced properties can be identified, this may permit a higher proportion of poorly soluble drug candidates to be successfully formulated as ASDs.…”
Section: Introductionmentioning
confidence: 99%
“…While the Taylor and Edgar groups have described design and in vitro testing of a number of new polysaccharide derivatives for ASDs of poorly soluble drugs 9 , 11 , 15 , 24 , 25 , no in vivo studies have been performed on formulations containing these polymers. The goal of this study was to evaluate in vivo absorption performance of two of these new polymers, selected from a larger group which were first evaluated in terms of their ability to inhibit crystallization during in vitro studies.…”
Section: Introductionmentioning
confidence: 99%